AFRICOM and the Burdens of Securitisation in Africa - Nyiayaana, Kialee; Nwankpa, Clare Ifeyinwa (European Scientific Journal, ESJ, 2022)
This article aims at analyzing the nature and role of the United States Africa Command (AFRICOM) in the governance security in Africa. It depended on secondary data, which were obtained from journals, newspapers, books, and annual reports on the activities of the Command. A combination of thematic, content and historical methods of data analysis was used to interpret and explain the nature, role, and challenges of AFRICOM in the governance of security in Africa. Guided by the theory of securitization, the results indicate that the nature of AFRICOM’s security governance reflects continuity and change in the United States’ militarism in Africa and the evolving character of the securitization order in the continent since the events of 9/11. The analysis shows that the securitization role of AFRICOM involves competitive militarisation strategically designed to contain the rising economic and political influence of China on the continent. Yet, its counterterrorism operations fall short of addressing the structural sources of Africa’s security predicaments. In these contexts, AFRICOM’s activities have had little or any significant impact on the protection of life and property in Africa. In fact, by articulating and reproducing Africa as security deficient and security dependent on the West, the concept and activities of AFRICOM broadly constitute a phase in the genealogies of coloniality of Western militarism and securitization in the continent.